2021
DOI: 10.1017/s0025315421000540
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of Ratabulus diversidens and Ambiserrula jugosa (Pisces: Platycephalidae) from continental shelf waters of south-eastern Australia

Abstract: The reproductive characteristics of co-occurring freespine flathead, Ratabulus diversidens, and mud flathead, Ambiserrula jugosa, that interact with fisheries across continental shelf waters of eastern Australia were examined. Samples were collected across three depth strata and two locations on a monthly basis over two years. Males of both species matured younger and at smaller total lengths (TL) than females. Estimated TL and age (years) at maturity (L50 and A50, respectively) of R. diversidens also varied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 67 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…All three species, along with other coexisting platycephalids, Ratabulus diversidens and Ambiserrula jugosa (Barnes et al ., 2021), displayed a similar reproductive characteristic of (a) asynchronous oocyte development, which potentially allows each individual to spawn multiple times within each spawning period (Lowerre‐Barbieri et al ., 2011) and (b) an extended spawning period spanning several months (potentially year‐round for P. caeruleopunctatus and P. grandispinis ). These risk‐adverse traits allow individuals to extend and maximise egg production across a spawning period (Lowerre‐Barbieri et al ., 2011; McBride et al ., 2013), enhancing the probability of successful reproduction during times of favourable oceanographic ( e.g ., temperature, current direction, strength) and ecological ( e.g ., types and levels of prey and predators) conditions that facilitate optimal dispersal and survival of developing eggs and larvae (Lambert & Ware, 1984; Lobel, 1989; Lowerre‐Barbieri et al ., 2011; McBride et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All three species, along with other coexisting platycephalids, Ratabulus diversidens and Ambiserrula jugosa (Barnes et al ., 2021), displayed a similar reproductive characteristic of (a) asynchronous oocyte development, which potentially allows each individual to spawn multiple times within each spawning period (Lowerre‐Barbieri et al ., 2011) and (b) an extended spawning period spanning several months (potentially year‐round for P. caeruleopunctatus and P. grandispinis ). These risk‐adverse traits allow individuals to extend and maximise egg production across a spawning period (Lowerre‐Barbieri et al ., 2011; McBride et al ., 2013), enhancing the probability of successful reproduction during times of favourable oceanographic ( e.g ., temperature, current direction, strength) and ecological ( e.g ., types and levels of prey and predators) conditions that facilitate optimal dispersal and survival of developing eggs and larvae (Lambert & Ware, 1984; Lobel, 1989; Lowerre‐Barbieri et al ., 2011; McBride et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The potential depth of spawning habitat of each platycephalid may reflect a further ecological adaptation to regional oceanographic conditions (Ciannelli et al ., 2015). Mature (including those in spawning condition and recently spawned) individuals of all three platycephalids, along with coexisting R. diversidens (Barnes et al ., 2021) and sillaginid species (Gray et al ., 2014), predominantly occurred in waters >30 m depth. Oceanographic model simulations have identified that broadcast spawning in waters 30–100 m deep is optimal for transporting developing eggs and larvae to inshore nursery habitats along the east coast of Australia, potentially benefitting population renewal (Cetina‐Heredia et al ., 2019; Everett et al ., 2017; Schilling et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations